2013
DOI: 10.1371/journal.pone.0071802
|View full text |Cite
|
Sign up to set email alerts
|

Copy Number Variation Analysis in Familial BRCA1/2-Negative Finnish Breast and Ovarian Cancer

Abstract: BackgroundInherited factors predisposing individuals to breast and ovarian cancer are largely unidentified in a majority of families with hereditary breast and ovarian cancer (HBOC). We aimed to identify germline copy number variations (CNVs) contributing to HBOC susceptibility in the Finnish population.MethodsA cohort of 84 HBOC individuals (negative for BRCA1/2-founder mutations and pre-screened for the most common breast cancer genes) and 36 healthy controls were analysed with a genome-wide SNP array. CNV-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 40 publications
1
38
1
Order By: Relevance
“…There are rare CNVs that are associated with early familial onset of breast cancers devoid of mutations of BRCA1/BRCA2 [64]. In individuals with familial BRCA1/2-negative breast and ovarian cancer, a CNV at 3p11.1 affects carcinogenesis; an intronic deletion in the EPHA3 receptor tyrosine kinase increases the fulminating risk of the disease (OR = 1.96) [65]. The deletion variant of a CNV at 8p22 including mitochondrial tumor suppression gene 1 (MTUS1) also decreases the risk for familial breast cancer [66].…”
Section: Breast Cancermentioning
confidence: 99%
“…There are rare CNVs that are associated with early familial onset of breast cancers devoid of mutations of BRCA1/BRCA2 [64]. In individuals with familial BRCA1/2-negative breast and ovarian cancer, a CNV at 3p11.1 affects carcinogenesis; an intronic deletion in the EPHA3 receptor tyrosine kinase increases the fulminating risk of the disease (OR = 1.96) [65]. The deletion variant of a CNV at 8p22 including mitochondrial tumor suppression gene 1 (MTUS1) also decreases the risk for familial breast cancer [66].…”
Section: Breast Cancermentioning
confidence: 99%
“…Recently, rare CNVs were shown to be important sources for interindividual variations in the susceptibility to familial BC [Gonzalez et al, 2005;Krepischi et al, 2012b;Pylkas et al, 2012;Kuusisto et al, 2013;Masson et al, 2014;Park et al, 2015]. Further, we have demonstrated that copy-neutral losses of heterozygosity are also an important class of structural variations and serve as biomarkers of prognostic value in a BC setting [Sapkota et al, 2013a].…”
mentioning
confidence: 79%
“…The disease results from the combined effects of genetic, environmental, reproductive, and lifestyle risk factors [Sehrawat et al, 2011; Sapkota et al, 2013a, b]. Single nucleotide polymorphisms (SNPs) identified through genome-wide association studies (GWAS) helped explain only a small proportion of genetic risk in BC [Stacey et al, 2007[Stacey et al, , 2008Kidd et al, 2008;Krepischi et al, 2012a;Kuusisto et al, 2013;Long et al, 2013;Michailidou et al, 2013;Sapkota et al, 2013bSapkota et al, , 2014. It is believed that additional variants need to be Key Words Association study · BRCA · Breast cancer susceptibility · Copy number variations · Copy number variation calling algorithm · Genetic predisposition · Germline DNA · Polygenic disease · Single nucleotide polymorphism · Sporadic breast cancer Abstract Breast cancer (BC) predisposition in populations arises from both genetic and nongenetic risk factors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…individuals collected from Tampere University Hospital in which index patients have been screened for variants in BRCA1, BRCA2, CHEK2, PALB2, BRIP1, RAD50, and CDH1 genes and for copy number variations on a genome-wide scale. 10,11 In one of these families, two CHEK2 variants, c.470T4C and c.1100delC, have been reported. 10 Seven other families were selected into this study based on the previously described high-risk hereditary BC criteria.…”
Section: Introductionmentioning
confidence: 99%